2007
DOI: 10.1128/jb.01806-06
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Mutation of an Essential Putative Glycoprotease Eliminates Autolysis in Staphylococcus aureus

Abstract: Our previous studies demonstrated that a putative Staphylococcus aureus glycoprotease (Gcp) is essential for bacterial survival, indicating that Gcp may be a novel target for developing antibacterial agents. However, the biological function of Gcp is unclear. In order to elucidate the reason that Gcp is required for growth, we examined the role of Gcp in bacterial autolysis, which is an important biological process for bacterial growth. Using both a spacp-regulated gcp expression strain and a TetR-regulated gc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 49 publications
1
28
1
Order By: Relevance
“…Depletion of yjeE and ygjD similarly gave rise to (at least a subset of) very enlarged cells that had defective morphologies, consistent with a link to cell envelope processes. It should be noted that conditional mutation of gcp in Staphylococcus aureus has also been linked to effects on cell wall turnover (74). In each case, the enlarged cells seen during yjeE and ygjD depletion showed a highly unusual pattern of DNA distribution that has only been seen previously when E. coli strains are starved for thymine.…”
Section: Discussionmentioning
confidence: 98%
“…Depletion of yjeE and ygjD similarly gave rise to (at least a subset of) very enlarged cells that had defective morphologies, consistent with a link to cell envelope processes. It should be noted that conditional mutation of gcp in Staphylococcus aureus has also been linked to effects on cell wall turnover (74). In each case, the enlarged cells seen during yjeE and ygjD depletion showed a highly unusual pattern of DNA distribution that has only been seen previously when E. coli strains are starved for thymine.…”
Section: Discussionmentioning
confidence: 98%
“…To investigate if the airSR TCS transcriptionally regulates the promoter of the crtOPQMN operon, we constructed a crt promoter-lux (luxABCDE) reporter using the pCY1006 vector (44), as previously described (45). The upstream crt promoter region was PCR amplified with primers Pcrt For-lux/Pcrt Rev-lux (listed in Table 2), purified, and digested with EcoRI and SmaI (NEB).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has been demonstrated that Clp protease activity affects the expression of regulators, including lytSR, lrgAB, arlRS and rat (Michel et al 2006), which are involved in the modulation of murein hydrolases. Recently, we have demonstrated that a putative glycoprotease (Gcp) modulates the process of S. aureus autolysis (Zheng et al 2007).…”
Section: Introductionmentioning
confidence: 99%